Bacterial diversity in cheese wastewater using Next-Generation Sequencing (NGS) - SOLIKAH ANA ESTIKOMAH; SURANTO SURANTO; ARI SUSILOWATI; MOHAMMAD MASYKURI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Estikomah SA, Suranto, Susilowati A, Masykuri M. 2024. Bacterial diversity in cheese wastewater using Next-Generation Sequencing (NGS). Biodiversitas 25: 482-490. Cheese wastewater (whey) has a high content of organic substances, including lactose, protein, and fat. The lactose in whey wastewater can also be used as a bacterial growth medium. Bacterial community structure is an essential aspect of microbial water quality. The bacterial diversity data obtained can then be used to evaluate the existence of bacteria that might be useful for making microbiological products. This research employs Next Generation Sequencing (NGS) technology to determine the diversity and abundance of bacteria based on 16S rRNA gene amplicons for further processing of whey wastewater. The NGS-based technique overcomes the limitations of conventional bacterial culture techniques. The effectiveness and accuracy of microbial diversity analysis employing NGS technology are high. The research method includes the steps of sample preparation, DNA extraction using a ZymoBIOMICS DNA Microprep Kit (D4300), PCR amplification of the V3-V4 16S rRNA gene region, DNA sequencing, and a bioinformatics-statistical analysis. The results show that bacterial diversity in whey wastewater was found to have an average number of Operational Taxon Units (OTUs) of 259 tags. The metagenomics study of the microbial community in whey wastewater successfully detected the dominant genus of bacteria, which can benefit the management of whey wastewater. The presence of Lactobacillus and Acetobacter confirms that cheese whey wastewater exists in Yogyakarta Province. Acetobacter can oxidize ethanol to produce acetic acid, a pungent odor characteristic that causes environmental pollution. On the other hand, the presence of Lactobacillus and Acetobacter shows that whey wastewater can be reprocessed to produce fermented beverages, thereby improving their value and minimizing the impact of environmental pollution.